The Store - Patterson, James, 1947-; DiLallo, Richard (New York : Little, Brown and Company, 2017)
Living in a world where all needs are anticipated and delivered by a powerful convenience retailer known as The Store, New York writers Jacob and Megan go undercover to expose The Store's secrets in ways that risk their lives.
Keywords: Stores, Retail -- Fiction; Undercover operations -- Fiction; Stores -- Fiction; Suspense fiction; Suspense fiction